RETRACTED ARTICLE: Intrapartum cardiotocogram monitoring between obstetricians and computer analysis. (18th October 2021) - Magawa, Shoichi; Tanaka, Hiroaki; Furuhashi, Fumi; Maki, Shintaro; Nii, Masafumi; Toriyabe, Kuniaki; Kondo, Eiji; Ikeda, Tomoaki
Abstract: We, the Editors and Publisher of The Journal of Maternal-Fetal & Neonatal Medicine, have retracted the following article: Shoichi Magawa, Hiroaki Tanaka, Fumi Furuhashi, Shintaro Maki, Masafumi Nii, Kuniaki Toriyabe, Eiji Kondo & Tomoaki Ikeda; Intrapartum cardiotocogram monitoring between obstetricians and computer analysis, The Journal of Maternal-Fetal & Neonatal Medicine (Author Accepted Version), 10.1080/14767058.2019.1615876 . The incorrect manuscript was provided by the authors resulting in a duplicate publication. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".